ABC3 Consensus Commented from the Perspective of the German Guidelines - Untch, M.; Augustin, D.; Ettl, J.; Haidinger, R.; Harbeck, N.; Lück, H.-J.; Lüftner, D.; Marmé, F.; Müller, L.; Overkamp, F.; Ruckhäberle, E.; Thill, M.; Thomssen, C.; Wuerstlein, R.; Marschner, N. (Geburtshilfe und Frauenheilkunde, 2016)
The Third International Consensus Conference for Advanced Breast Cancer ABC3 on the diagnosis and treatment of advanced breast cancer was held in Lisbon from 5 to 7 November 2015. This year the focus was the treatment of metastatic breast cancer (stage IV) – including the patient perspectives. Important topics were questions relating to quality of life, the care for long-term survivors as well as the management of disease-related symptoms and treatment-based side effects. The use of standardised tools to assess individual treatment success and the benefits of new substances were important points for discussion. The diagnosis and treatment of inoperable locally advanced breast cancer were discussed two years ago during the ABC2 consensus 1. A working group of German breast cancer experts commented on the results of the ABC panellists, paying particular attention to the German guidelines (AGO, S3, DGHO) on the diagnosis and treatment of breast cancer 2, 3, 4, 5 in Germany.
Keywords: ABC3 Consensus; Metastatic breast cancer; System therapy; Guidelines